Pengetahuna Perawat dalam Pembagian Triase Diunit Gawat Darurat RSUP Prof Dr. R.D Kandou Manado - Kawengian, Amelia Magdalena; Puspitasari, Yenny (Green Publisher Indonesia, 2025)
The implementation of triage in the Emergency Unit (ER) has an important role in determining the priority of patient handling quickly and appropriately. Errors in the division of triage such as under triage and over triage can have a serious impact on patient safety and service quality. One of the factors that affect the accuracy of triage division is the level of knowledge of nurses. Therefore, increasing nurses' knowledge is a strategic step to support accurate clinical decisions in the ER of Prof. Dr. R. D. Kandou Manado Hospital. This research aims to increase nurses' knowledge in the distribution of triage in the Emergency Unit of Prof. Dr. R. D. Kandou Manado Hospital through continuous training and evaluation activities. This study uses a descriptive method with a pre-test and post-test approach for implementing nurses in the ER. The number of respondents was 20 nurses who were selected in total sampling. The intervention was in the form of providing training on the concept, principles, and application of the triage system using the Emergency Severity Index (ESI) standard. Data were analyzed descriptively to see an increase in knowledge scores before and after the intervention. The results showed an increase in the average knowledge score of nurses from 65.5 before training to 88.7 after training. Most respondents experienced an increased understanding of patient priority criteria, critical vital signs, and determination of appropriate triage levels. Triage training activities have proven to be effective in increasing the knowledge of nurses in the Emergency Unit of Prof. Dr. R. D. Kandou Manado Hospital. Regular training and periodic supervision are needed to maintain the consistency of accurate triage implementation and improve the quality of emergency services.